Synthesis and characterisation of lamellar ZnS nanosheets containing intercalated diamines - Sperinck, S.; Becker, Thomas; Wright, Kate; Richmond, William (Kluwer Academic Publishers, 2009)
A solvothermal method has been used to preparehybrid inorganic-organic composites with a lamellar structure in which layers of wurtzite ZnS are separated by intercalated diamine molecules. A hybrid composite prepared with diethylenetriamine has been isolated and characterisedand its structure and properties compared with those of the composite prepared using ethylenediamine. Comparative structural and morphological studies of the two lamellar hybrid composites are described on the basis of powder XRD, electron and scanning probe microscopies and thermal analysis of the materials.